Direct Comparison of Multidimensional Clinical Assessment Tools: Sensitivity to Concussion in Student Athletes. (26th July 2019) - Wilmoth, K; Mau, K; Guzowski, N; Brett, B; McCrea, M; Nelson, L
Abstract: Purpose: Consensus guidelines recommend multidimensional assessment for concussion diagnosis and management. Among cognitive, oculomotor, and postural stability, it remains unclear which modalities perform best in the acute/subacute periods. We conducted a direct comparison to identify those with the strongest sensitivity to sport-related concussion. Methods: High school and collegiate football players (aged 14–24) completed preseason baseline assessments. Concussed (n=91) and matched non-concussed teammates (n=85) underwent repeat testing at 48 hours, 8 days, and 15 days post-injury. Postconcussive symptoms (SCAT-3 symptom severity), cognition (Standardized Assessment of Concussion, Immediate Post-Concussion and Cognitive Testing, Trail Making Test, Wechsler Adult Intelligence Scale-IV Processing Speed Index), oculomotor functioning (King-Devick Test), and postural stability (Balance Error Scoring System) were compared using Cohen's d and Receiver Operating Characteristic analyses. Results: Symptom severity had the greatest sensitivity at 48 hours and 8 days post-injury (Cohen's d=1.43 and 0.53, AUC=.93 and .63, p<.01). Of the performance-based assessments, BESS was most sensitive to SRC at 48 hours post-injury (Cohen's d=.74, AUC=.70, p<.01). Oculomotor and cognitive testing via ImPACT, WAIS-IV PSI, and TMT-A were sensitive to a lesser degree (Cohen's d=.35–.58, p<.05). Verbal memory was the only significant performance-based assessment at days 8 and 15, with small-to-medium effect sizes (Cohen's d=.37 and .44, p<.05). Other cognitive measures (SAC, TMT-B) were not sensitive to SRC across timepoints (p>.05). Conclusion: We observed heterogeneity in clinical assessment performance such that the clinical domains strongest in the initial days post-injury (symptom severity, balance) were less sensitive at later follow-up, supporting the potential need for multidimensional assessment.